Culture, migration, and health communication in a global context - Mao, Yuping (Assistant professor of communication studies); Ahmed, Rukhsana (Routledge, 2017)
"Both international and internal migration brings new challenges to public health systems. This book aims to critically review theoretical frameworks and literature, as well as discuss new practices and lessons related to culture, migration, and health communication in different countries. It features research and applied projects conducted by scholars from various disciplines including media and communication, public health, medicine, and nursing. "- Resumé vydavatel
Keywords: komunikace (sdělování); veřejné zdraví; veřejné zdraví -- socialní aspekty; emigranti; imigranti; human communication; public health; public health -- social aspects; emigrants; immigrants; kolektivní monografie; elektronické knihy; collective monographs; electronic books